Long-term experience with debulking surgery in extensive hepatic alveolar echinococcosis: A case series and literature review - Mohsen Aliakbarian; Marcello Di Martino; Sara Saeidi (Asian Pacific Journal of Tropical Medicine, 2022)
Objective: To assess the role of debulking surgery in extensive hepatic alveolar echinococcosis (HAE). Methods: Five cases of extensive HAE undergoing debulking surgery with their long-term follow-ups were reported. Additionally, a systematic review was carried out. Results: The average age of patients in the study was (50.8±17.1) years (range 36 to 77 years). Three cases were female. The median follow-up period was 61 months (range 12 to 84 months). Left liver resections were performed in 2 cases and right hemihepatectomies were undertaken in 2 cases. Two patients (cases 2 and 4) developed early surgical complications, while one of them (case 4) who suffered from the recurrent sub-hepatic abscess died at 12 months postoperatively. Conclusions: This study highlights the importance of debulking surgery for the management of complex symptomatic HAE lesions in patients with no curative option available.